DASAR NEGARA DAN TAQIYYAH POLITIK PKS - Rokhmad, Abu (IAIN Walisongo Semarang, 2014)
This article studied about the relationship between Partai Keadilan Sejahtera(PKS/the Prosperous Justice Party) and Pancasila as the stateâs philosophy. PKSdidnât have the experience of the struggle of Indonesian independence and thedifficult period of the Pancasila formulation. PKS was born after Pancasilaconvinced as the national agreement. The political attitude of PKS to Pancasila asthe stateâs philosophy is still indistinct. PKS viewed as political party that hide theirtruly intent: between receiving Pancasila and implementing islamic shariâah. Theaspiration of implementing islamic shariâah has been concealing in vision andmission as well as in the heart of PKSâs cadres. The aspiration will be done bypeaceful and constitutional ways.Artikel ini mengkaji relasi Partai Keadilan Sejahtera (PKS) dengan Pancasilasebagai dasar negara. PKS tidak mengalami perjuangan meraih kemerdekaan danmasa-masa sulit perumusan Pancasila. PKS lahir setelah Pancasila diyakinisebagai perjanjian suci kebangsaan. Sikap PKS terhadap Pancasila sebagai dasarnegara masih mengambang. Ia dipandang menyembunyikan maksud hati yangsebenarnya: antara menerima Pancasila atau menegakkan syariat Islam. Cita-citamenegakkan syariat Islam tersimpan dalam visi, misi dan hati para kader PKS,yang akan dilakukan secara damai dan konstitusional.